2016
DOI: 10.1371/journal.pone.0159684
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Release, ROS Generation and Toxicity of Ni and NiO Micro- and Nanoparticles

Abstract: Occupational exposure to airborne nickel is associated with an elevated risk for respiratory tract diseases including lung cancer. Therefore, the increased production of Ni-containing nanoparticles necessitates a thorough assessment of their physical, chemical, as well as toxicological properties. The aim of this study was to investigate and compare the characteristics of nickel metal (Ni) and nickel oxide (NiO) particles with a focus on Ni release, reactive oxygen species (ROS) generation, cellular uptake, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
102
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 42 publications
14
102
1
Order By: Relevance
“…Soesetijo et al have recently demonstrated enhanced apoptosis of gingival fibroblasts induced by nickel released from nickel-chromium alloys [1]. Latvala et al found that nickel can enhance reactive oxygen species generation, cytotoxicity and genotoxicity in human alveolar epithelial cell line A549 [14]. Our present and previous results [13] are in concordance with the aforementioned data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Soesetijo et al have recently demonstrated enhanced apoptosis of gingival fibroblasts induced by nickel released from nickel-chromium alloys [1]. Latvala et al found that nickel can enhance reactive oxygen species generation, cytotoxicity and genotoxicity in human alveolar epithelial cell line A549 [14]. Our present and previous results [13] are in concordance with the aforementioned data.…”
Section: Discussionsupporting
confidence: 93%
“…It has been well established that orthodontic appliances release nickel into the artificial saliva and into the saliva of oral cavity [1,6,7,14]. Indeed, Faccioni et al found a higher nickel concentration in the oral mucosa cells of patients treated orthodontically in comparison to controls [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the cell viability assay, Ni concentrations of 0.15 and 0.32 μg cm −2 induced substantially decreased viability (approximately 45%) after 48 hours post‐exposure in ALI, when compared to the control. In comparison with a previous study (Latvala et al, ), these results suggest that ALI exposure may result in more sensitive conditions when compared to submerged exposures, although different cell types were used.…”
Section: Discussioncontrasting
confidence: 42%
“…is the final product of lipid peroxidation process [25] and is still routinely used as a marker for oxidative stress induced by different toxicants [26]. Several works conclusions have agreed about the mechanism of NiNPs in inducing the toxicity in vivo [19] and in vitro [22]- [18] which is the inducting oxidative stress through elevating the levels of reactive oxygen species (ROS). In the present investigation, NiNPs have caused a significant (P≤0.05) dose dependent elevation of serum creatinine in comparison to the control (Fig.2).…”
Section: Resultsmentioning
confidence: 99%
“…The increased production of Ni-containing nanoparticles necessitates a thorough assessment of their toxicological properties [22].…”
Section: Introductionmentioning
confidence: 99%